Rationale for Spiritually Oriented Cognitive Processing Therapy for Moral Injury in Active Duty Military and Veterans With Posttraumatic Stress Disorder. Issue 2 (February 2017) - Koenig, Harold G.; Boucher, Nathan A.; Oliver, Rev. John P.; Youssef, Nagy; Mooney, Scott R.; Currier, Joseph M.; Pearce, Michelle
Abstract : Abstract: Wartime experiences have long been known to cause ethical conflict, guilt, self-condemnation, difficulty forgiving, loss of trust, lack of meaning and purpose, and spiritual struggles. "Moral injury" (MI) (also sometimes called "inner conflict") is the term used to capture this emotional, cognitive, and behavioral state. In this article, we provide rationale for developing and testing Spiritually Oriented Cognitive Processing Therapy, a version of standard cognitive processing therapy for the treatment of MI in active duty and veteran service members (SMs) with posttraumatic stress disorder symptoms who are spiritual or religious (S/R). Many SMs have S/R beliefs that could increase vulnerability to MI. Because the injury is to deeply held moral standards and ethical values and often adversely affects spiritual beliefs and worldview, we believe that those who are S/R will respond more favorably to a therapy that directly targets this injury from a spiritually oriented perspective. An evidence-based treatment for MI in posttraumatic stress disorder that not only respects but also utilizes SMs' spiritual beliefs/behaviors may open the door to treatment for many S/R military personnel.